PENGARUH NILAI PERUSAHAAN TERHADAP KEPEMILIKAN BLOCKHOLDER: PERUSAHAAN DI BEI 2005-2008 - Ariyani, Vivi (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2012)
Value of firms may affect blockholder ownership, when a blockholder wants to retain a large shareholding on the basis of alignment of incentives. This study examines the influence of firm value measured with a simple Tobin's Q to the blockholder ownership (measured from the fraction of shares controlled by large shareholders) of the 53 companies in Indonesia in the period 2005-2008. By using regression, the study found that there was the influence of firm value toward blockholder ownership in Indonesia. It is consistent with the results of the research conducted by Myers and Majluf, 1984; La Porta et al., 2000 stating that firm value has a positive effect on blockholder ownership.